A legacy of genetic entanglement with wolves shapes modern dogs - Audrey T. Lin; Regina A. Fairbanks; Jose Barba-Montoya; Hsiao-Lei Liu; Logan Kistler (Proceedings of the National Academy of Sciences, 2025)
Dogs evolved through interactions between people and gray wolves during the Late Pleistocene and have been ubiquitous in human societies ever since. Instances of wolf-to-dog introgression are rare, but adaptive introgression has been shown in association with high-altitude survival. Any widespread gene flow, however, has fallen below thresholds of detection in genome-wide statistical assessments. To reexamine evidence of dog–wolf gene flow, we analyzed 2,693 published dog and wolf genomes and combined highly sensitive local ancestry inference and phylogenomic analyses of nuclear genes, mitochondrial genomes, and Y-chromosome sequences. Although dogs and wolves segregate decisively at the nuclear level, no individual nuclear gene tree supports dog monophyly. Uniparental markers show mixed and interleaved dog and wolf clades with strong support and incongruent phylogenetic topologies. Using local ancestry inference, we find that 64.1% of modern breed dogs carry wolf ancestry from admixture that occurred nearly a thousand generations ago on average and now covers ~0.14% of their individual nuclear genomes. Among modern free-living village dogs (n = 280), 100% of analyzed genomes carry wolf ancestry. We find that wolf ancestry in dog breeds correlates with functional traits including size, breed category, and personality characteristics. In village dogs, wolf ancestry is enriched at olfactory receptor genes, suggesting adaptive introgression for sensory acuity that may have helped these free-living dogs survive in more challenging environments. In total, dog–wolf admixture has likely been an important factor in shaping the evolution of modern dogs.